Ethnic Residential Patterns in Urban England and Wales, 2001–2011: A System‐Wide Analysis. (13th January 2015) - Johnston, Ron; Poulsen, Michael; Forrest, James
Abstract: Many cities world‐wide are becoming increasingly multi‐cultural and multi‐ethnic in their population composition. However, little attention has been paid in the massive literature on the resultant residential mosaics as to whether the outcomes of those changes are common across a national urban system or whether there are local variations – or to the factors likely to influence any such variations. Using small‐area data for towns and cities in England and Wales from the 2001 and 2011 censuses this paper finds clear relationships between the relative size of an urban area's non‐White ethnic minority population and the mix of different types of neighbourhood according to their ethnic composition – findings that have clear relevance for the development of the emerging countries' multi‐cultural character.